Seni Kriya Dalam Kehidupan Manusia - Kusmadi Kusmadi (Institut Seni Indonesia Surakarta, 2010)
Craftmanship art as human cultural creation results in material form reflects the level of civilization in their ages. Functional value as daily activity support becomes the main special characteristic. Visualization of the art tends to aesthetic, expressive and symbolic expression of the creator's soul as the influence of refine arts transformation in general. Craftmanship is closely related with materials, technique and processes in which stressing high patience, precise and thorough attitudes because handcraft, besides conceived as an art closely related with handcraft as one of its special characteristic, it is also the concrete result of an ability between the skills of the creator (craftmanship) and the instruments as the revealer of the creativity idea. Craftmanship has been reaching on classical level such noble creation as puppets, batik, and carved objects which are necessarily to be preserved and developed for the next generation for not to be extinct, ate by the fast of modernization dynamics.